PENGEMBANGAN NUTRASEUTIKAL SEREAL DAUN KELOR (MORINGA OLEIFERA L.) DENGAN TEPUNG GARUT (MARANTA ARUNDINACEAE L.) SEBAGAI PENGIKAT - Rani, Karina Citra; Parfati, Nani; Putri, Pragita; Regina, Elisabeth (Jurnal Farmasi Indonesia, 2019)
Moringa oleifera leaves potential to be developed as nutraceutical product because it contains amino acids, carbohydrates, fat, fiber, vitamin, and, minerals. Cereal is one of the nutraceutical products which can be developed using Moringa oleifera leaves as main ingredients. This research was conducted to develop Moringa oleifera leaves into dry instant cereals granules. The manufacturing process of this cereal was conducted using a wet granulation method. There are two formulas of Moringa oleifera leaves cereals which was developed in this research, formula 1 (without the arrowroot powder) and formula 2 (with arrowroot powder as a binder). Cereals of Moringa oleifera leaves in this study, then subjected to several evaluations such as physical characteristics of granules, viscosity, pH, proximate analysis based on SNI of cereal (SNI 01-4279-1996) (water content, coarse  fiber, levels of ash, protein, fat, and carbohydrates), and the levels of metals (Pb and Cu). The results showed that formula 1 and formula 2 fulfil the specification of physical characteristics of granules, viscosity, and pH. The results of proximate analysis (levels of ash, protein, carbohydrates, and metal content) revealed that both formula met the requirement of SNI. The results of fat content in cereals showed that formula 2 met the requirement of SNI, hence formula 2 did not meet the requirement. Based on these results, it can be inferred that Moringa oleifera leaves cereals which using arrowroot as a binder (formula 2) has fulfilled the nutrition requirements of SNI.